Policy Study Early Childhood Education to Elementary School Transition - Pratiwi, Dewa Ayu Anom; Sujaelanto, Sujaelanto (International Journal of Multidisciplinary Sciences, 2024)
There has been a wide gap between the approach to education in kindergarten/early childhood education and elementary school. It has contributed to the suboptimal children's learning process when they are in elementary school. This research aimed to provide an understanding and steps to be taken to eliminate the gap between educational approaches in early childhood education and elementary school. Researchers chose literature review as the research method, which went through the stages of designing, conducting, analyzing, and writing the reviews. The research showed that the fundamental thing about the learning transition from kindergarten/early childhood education to elementary school was that all parties had the same understanding and perception that children aged 7 – 8 years in elementary school were still in the early childhood phase. At that age, they should learn in a fun way to introduce various basic concepts taught through games. Furthermore, collaborative sharing between kindergarten/early childhood education and elementary school teachers so that everyone could understand each other’s position. Furthermore, the will to change following the learning pattern with kindergarten/early childhood education – elementary school transition strategy, which in this case was more dominant in intervening with teachers at the elementary education level. It means that elementary teachers had to learn more from kindergarten/early childhood education teachers in terms of organizing fun learning.